The Company Liability for Violation an ESG Compliance That Affect Environmental Damages - Zahra Awaliany Safitri; Heru Sugiyono (Trunojoyo Madura University, 2025)
As legal subjects, corporations in Indonesia not only have economic obligations but also have a responsibility to support sustainable development. This paper examines corporate legal liability for violations of compliance with Environmental, Social, and Governance (ESG) principles that result in environmental damage. The purpose of this research is to analyze the role of ESG implementation in strengthening corporate legal compliance and governance, as well as to review corporate accountability mechanisms through a case study of PT Soedali Sejahtera, which polluted the Getih River in Surabaya due to the absence of UKL-UPL environmental documents. The research employs a normative juridical method by examining regulations such as Law No. 32 of 2009 concerning Environmental Protection and Management (UUPPLH), Government Regulation No. 47 of 2012 concerning Corporate Social and Environmental Responsibility (TJSL), and Financial Services Authority Regulation No. 51/POJK.03/2017 as a framework for sustainable finance. The results show that the integration of ESG principles strengthens transparency, accountability, and corporate legal compliance, where the integration of ESG can serve as a strategic instrument in realizing sustainable and responsible business practices.